Tijn... Tino - Ellemers, Carina (Netherlands, 2007)
Ellemers follows Tijn van Dijk, the adopted photographer as he returns to his home country of Indonesia after finishing university, reverts to his birth surname and gets married and fathers a child there.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films